2016
DOI: 10.3892/etm.2016.3282
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin induces cell apoptosis via activation of the p53/Bcl-2/caspase-9 pathway in hepatocellular carcinoma cells

Abstract: Abstract. Chrysin is a major active ingredient of flavonoids, known to exhibit protective effects against various types of cancer. However, the anticancer role of chrysin against hepatocellular carcinoma (HCC) and the underlying molecular mechanisms remain unclear. In order to evaluate the effects of chrysin on cell viability and apoptosis in human HCC, HepG2 and QGY7701 cells were used in the present study. Cell viability was monitored using an MTT assay. In addition, an Annexin V-fluorescein isothiocyanate/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 24 publications
3
34
0
1
Order By: Relevance
“…14,16,32 In the present study, chrysinNPs were observed to have anticancer effects in A549-derived tumor tissues. In fact, chrysin-NPs inhibited cell proliferation and induced apoptosis in tumor tissues ( Figure 6).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…14,16,32 In the present study, chrysinNPs were observed to have anticancer effects in A549-derived tumor tissues. In fact, chrysin-NPs inhibited cell proliferation and induced apoptosis in tumor tissues ( Figure 6).…”
Section: Discussionmentioning
confidence: 87%
“…Chrysin is a natural active component found in various herbs, mushroom, and propolis 2 and has anti-inflammatory, 3,4 antiaging, 5 antiviral, 6 antioxidant, [7][8][9] antidiabetes, 10 antiaromatase, 11,12 and anticancer [13][14][15][16] activities. Accordingly, it is widely held that chrysin has potential pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, chrysin suppresses development and progression of cancer cells originating from prostate, skin, colon, breast, liver, and lung (Kasala et al, ). Chrysin induces apoptosis by stimulating pro‐apototic proteins and cleavage of caspases in hepatocellular carcinoma cells (Zhang et al, ). Chrysin inhibits hypoxia‐induced survival of breast cancer cells by inactivating hypoxia‐induced STAT3 phosphorylation and reducing VEGF expression to control metastatic progression and tumor growth (Lirdprapamongkol et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of HP53 mutation in the plasma could be indicative of HCC nodules [16]. Zhang et al have suggested that chrysin (natural flavonoid) may promoted HCC cell apoptosis via activation of the p53/Bcl2/caspase-9 apoptotic signalling pathway [17].…”
Section: Discussionmentioning
confidence: 99%